Modeling vernal pool hydrologic regimes and assessing their sensitivity to climatic and land-use change - Pyke, Christopher R. (2002)
Ecological systems are sensitive to the spatial and temporal distribution of environmental variability. They respond to changes in variability with changes in population processes, species interactions, and, ultimately, species persistence. Assessing the impact of climate and land-use changes requires an understanding of the mechanisms linking environmental conditions to ecological processes. The distribution of environmental conditions available to species across a region is a function of interactions between ecological tolerances and the spatial and temporal distribution of climate and habitat. This dissertation explored the impact of interactions between changes in the geographic distribution of habitat and climate for rain-fed ephemeral, depressional wetlands (vernal pools) in the Central Valley of California. Several authors have suspected that these habitats will be particularly sensitive to climatic change, and they contain a disproportionate number of rare, endemic, and endangered species. This dissertation used simulation modeling to (1) evaluate hydrologic regimes under historic climates, (2) modify hydrologic regimes based on regional climate predictions, and (3) evaluate land-use and climate change interactions. Modeling results suggest that vernal pool hydrologic regimes exhibit non-linear changes over geographic space and reflect more intense changes in ecologically-relevant conditions than might be suggested by the gradient in precipitation alone. Consideration of climate change impacts in the absence of land-use change (i.e., habitat loss) indicates that vernal pools could experience either a small reduction in annual hydroperiod (cooler, lower precipitation conditions) or, more likely, a significant increase in the annual duration of flooding (warmer, higher precipitation conditions). However, these region-wide responses change significantly when potential land-use change and associated habitat loss are considered. A bias in the distribution of reserve lands toward drier areas in the Central Valley results in a net shift toward drier, shorter-lasting, and less predictable vernal pools even under wetter climatic conditions. This research demonstrates that interactions between land-use and climate change can result in significant differences in the magnitude and direction of impacts compared to those predicted for either variable alone. This finding suggests that climate change impact assessments need to explicitly consider the interactions between climate and land-use in assessing future scenarios.